2005
DOI: 10.1177/0886260505278106
|View full text |Cite
|
Sign up to set email alerts
|

Courtship Violence Using Couple Data

Abstract: This study examined courtship violence using couple data. Participants were 50 heterosexual dating couples with at least one member of the couple being a university student. Using the Conflict Tactics Scales 2 (CTS2), both members of a couple reported on received and inflicted physical and psychological violence. The prevalence of physical aggression depended on how violence was defined. On the CTS2, 60% of couples were considered physically violent when within-couple agreement was not considered; this dropped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
25
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 33 publications
6
25
0
1
Order By: Relevance
“…However, the results did not show any differences between the male and female reports on psychological aggression towards their partners. In their study, Perry and Fromuth (2005) utilised the Conflict Tactic Scale-Revised which was completed by both partners; this gave the frequencies of both received and performed psychological aggression, Similar to the findings of other researchers. The female self-reported a greater likelihood of psychological aggression against their male partners than the males.…”
Section: Higher Psychological Aggression In Women Compared In To Mensupporting
confidence: 52%
See 1 more Smart Citation
“…However, the results did not show any differences between the male and female reports on psychological aggression towards their partners. In their study, Perry and Fromuth (2005) utilised the Conflict Tactic Scale-Revised which was completed by both partners; this gave the frequencies of both received and performed psychological aggression, Similar to the findings of other researchers. The female self-reported a greater likelihood of psychological aggression against their male partners than the males.…”
Section: Higher Psychological Aggression In Women Compared In To Mensupporting
confidence: 52%
“…In addition, the reports by the participants' seemed to suggest that women could be more psychologically aggressive than men. As well as in their study, Perry and Fromuth (2005) completed the Conflict Tactic Scale-Revised and found that female reported a greater likelihood of psychologically aggression against their male partner than the males. Moreover, women's sum and quantity perpetrations of psychological aggression were found to be higher than the sums and quantity of victimization by psychological aggression.…”
Section: Higher Psychological Aggression In Women Compared In To Menmentioning
confidence: 99%
“…On the other hand, some of the extant literature has provided support for gender similarities in motives for dating violence (Elmquist et al, in press; Perry & Fromouth, 2005; Shorey et al, 2010). Perry & Fromuth (2005) examined dating violence in a college sample of fifty heterosexual couples and found gender similarities for the motives of anger, retaliation, jealousy and/or control, and self-defense.…”
mentioning
confidence: 99%
“…Perry & Fromuth (2005) examined dating violence in a college sample of fifty heterosexual couples and found gender similarities for the motives of anger, retaliation, jealousy and/or control, and self-defense. Elmquist and colleagues (in press) demonstrated that, with the exception of retaliation and expression of negative emotions (i.e., anger), gender symmetry exists for a majority of the motive categories (e.g., jealousy, power/ control, and self-defense).…”
mentioning
confidence: 99%
“…A second limitation of the current study involves measuring IPV through participants’ self-reports of victimization on a 2-item screening instrument. Although self-report is arguably the best single method for detecting IPV victimization, underreporting may result from discrepancies in interpretation of item content or personal definitions of victimization (e.g., Perry & Fromuth, 2005). Screening instruments similar to items used in the current study tend to have good specificity, but lower sensitivity than more comprehensive measures (Nelson, Bougatsos, & Blazina, 2012).…”
Section: Discussionmentioning
confidence: 99%